PENGARUH PERPUTARAN AKTIVA TETAP, PERPUTARAN PERSEDIAAN, DAN PERPUTARAN PIUTANG TERHADAP ECONOMIC PERFORMANCE - Daniel Rahandri (Universitas Muhammadiyah Tangerang, 2020)
The purpose of this study was to determine the effect of fixed assets turnover, inventory turnover, and accounts receivable turnover on economic performance in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The periode time of the research is 5 years that is periode 2014 -2018 Population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. Data collection method used was technique purposing sampling. The results showed that the rotation of fixed assets had no effect on economic performance. While inventory turnover and accounts receivable turnover affect the economic performance. and the turnover of fixed assets, inventory turnover, and accounts receivable turnover together affect the economic performance.